Mobility Patterns of Cooking Pots in the Beersheba Valley during the Iron Age II - Ben-Shlomo, David (Zeitschrift des Deutschen Palästina-Vereins, 2024)
The Beersheba Valley area in the northeastern Negev, Israel, is a marginal area in the Southern Levant, and was probably part of the Kingdom of Judah during the Iron Age IIB-C (ca. 800-586 B.C.E.). Previous studies as well as a new large-scale compositional and technological study of nearly 300 Iron Age II common type cooking vessels from this region during the Iron Age II indicate that the vast majority of these vessels were imported from neighboring regions. Apparently, production centers of cooking pots located in the Judean Central Hills and Shephelah distributed cooking pots to this region located some 50km to the south. Another group of Edomite type cooking pots was imported from the eastern Negev or Aravah area, over 50km to the southeast. Only the minority of the cooking pots were produced in the Beersheba Valley itself. Other pottery forms in the same sites have a smaller proportion of non-local origin. This is a somewhat surprising phenomenon since ancient cooking ware is usually assumed to be locally made in a household- or local production mode, rarely associated with trade. The dynamics of inter-regional importations and plausible specialization of cooking pots are better defined and several explanations are suggested for this high mobility. The results are also discussed in relation to the distribution, typology as well as chronology of the vessels.